Highly skilled international migration, STEM workers, and innovation - Anelí Bongers; Carmen Díaz Roldán; José L. Torres (Economics: The Open-Access, Open-Assessment Journal, 2022)
This article studies the implications of highly skilled labor international migration in a two-country dynamic stochastic general equilibrium model. The model considers three types of workers: Science, Technology, Engineering, or Mathematics (STEM) workers, non-STEM college educated workers, and non-college educated workers. Aggregate productivity in each economy is a function of innovations, which can be produced only by STEM workers. The model predicts (i) the existence of a wage premium of STEM workers relative to non-STEM college educated workers, (ii) the skill wage premium is higher in the destination country and increases with positive technological shocks, (iii) a reduction in migration costs increases output, wages, and total labor in the destination country, with opposite effects in the country of origin, and (iv) high skilled immigrants reduce skilled native labor and do not affect unskilled labor. Finally, a migration policy designed to attract STEM workers generates similar effects to a positive aggregate productivity shock.
Keywords: F43; J61; O31; 330; dynamic stochastic general equilibrium models; innovation; labor migration; migration policy; STEM workers